HuangQin Decoction Attenuates CPT-11-Induced Gastrointestinal Toxicity by Regulating Bile Acids Metabolism Homeostasis - Wang, Xu; Cui, Dong-ni; Dai, Xiao-min; Wang, Jing; Zhang, Wei; Zhang, Zun-jian; Xu, Feng-guo (Frontiers in Pharmacology, 2017)
Irinotecan (CPT-11) is a potent chemotherapeutic agent, however, its clinical usage is often limited by the induction of severe gastrointestinal (GI) toxicity, especially late-onset diarrhea. Huangqin Decoction (HQD), commonly used for the treatment of gastrointestinal ailments, has been proved could significantly ameliorate the intestinal toxicity of CPT-11. To reveal the mechanisms of CPT-11-induced toxicity and the modulation effects of HQD, a previous untargeted metabolomics study was performed and the results indicated that HQD may protect the gastrointestinal tract by altering the metabolism of bile acids (BAs). Nevertheless, the untargeted assays are often less sensitive and/or efficient. In order to further confirm our previous findings, here in this paper, serum and tissues metabolic profiles of 17 BAs were analyzed using LC-MS/MS based targeted metabolomics. The results indicated that serum and tissues levels of most BAs were significantly decreased after CPT-11 administration, except some hydrophobic BAs. Co-treatment with HQD could markedly attenuate CPT-11 induced GI toxicity and reverse the alterations of hydrophobic BAs. Despite the fact that the BAs pool size remained unchanged, the balance of BAs had shifted leading to decreased toxicity after HQD treatment. The present study demonstrated for the first time that the precise interaction between HQD, CPT-11 induced intestinal toxicity and BAs’ homeostasis.